KARAKTERISTIK FISIKOKIMIA DAN SENSORIS MINUMAN COKELAT INSTAN DENGAN METODE FOAM MAT DRYING BERDASARKAN VARIASI KONSENTRASI MALTODEKSTRIN - Jannah, Ulfa Nur; Hersoelistyorini, Wikanastri; ., Nurrahman (Jurnal Pangan dan Gizi, 2024)
Instant chocolate drink is a beverage made from cocoa powder and other ingredients, such as sweeteners and milk, to enhance flavor and nutritional value. The production of instant chocolate drinks at TTP Nglanggeran still uses a simple process, mixing raw materials with a blender, resulting in low product solubility. Therefore, another method needs to be applied. One method that can be used is the foam mat drying process with varying concentrations of maltodextrin, as maltodextrin can improve the solubility of powdered drinks. The purpose of this study is to determine the effect of the foam mat drying method with variations in maltodextrin concentration on the physicochemical and sensory characteristics of instant chocolate drinks. The research method used is a Completely Randomized Design (CRD) with a single factor, namely the addition of maltodextrin at concentrations of 0, 5, 10, 15, and 20%, with each treatment repeated five times. The research procedure consists of three process stages: cocoa powder modification, instant chocolate drink production, and physicochemical and sensory analysis. Variations in maltodextrin concentration in the production of instant chocolate drinks using the foam mat drying method affect yield, solubility, antioxidant activity, and sensory characteristics of color but do not affect moisture content, or sensory characteristics of aroma, taste, and texture. Compared to the TTP Nglanggeran product, the instant chocolate drink from this study has advantages in moisture content percentage, solubility, and sensory values, with better scores; however, the antioxidant activity percentage is lower due to some antioxidant compounds being damaged by the foam mat drying process. The best treatment for the instant chocolate drink in this study was obtained with 20% maltodextrin addition, resulting in a yield of 26.97%, solubility of 86.88%, moisture content of 3.19%, antioxidant activity of 37.11%, and an average sensory score of 4.8.